Performa guru dalam perspektif kepemimpinan kepala sekolah dan lingkungan kerja - Sance K. M. Waromi; Rony Setiawan (Universitas Kristen Maranatha, 2026)
Teacher performance is one of the essential elements for the continuous improvement of education quality. This performance can be influenced by various organizational factors, including the work environment and leadership of the principal. This research has a scientific objective, namely to analyze the effect of these two variables on teacher performance at SMA Negeri 1 Timika using a quantitative associative research design, conducted with 49 civil servant teachers from the school as respondents. A closed questionnaire survey was one of the main techniques used to obtain all the targeted research data. Teacher performance was proven to be a positive result of the principal's leadership, which confirms that the direction, guidance, and support of leaders have an important influence on improving the performance of their subordinates. Teacher performance was also proven to be a positive result of the work environment, which indicates that a conducive work environment, especially harmonious working relationships, also strengthens teacher performance. Simultaneously, these two variables explain more than half of the variation in teacher performance, thus showing that organizational factors contribute substantially to the effectiveness of educators' work. These findings conclude that optimal teacher performance is the positive result of competent leadership and a conducive work environment. The implications of this study emphasize the need to strengthen school management, improve working conditions, and provide more optimal managerial support to encourage the continuous improvement of teacher professionalism.